Percepción visual en el proceso de lectura - Quimbita Loma, María del Carmen (2023)
Reading is a process acquired from the earliest years of a child, in which intervenes one of the main organs that the human being has: the sight; the selective visual attention to environmental factors around them have a closely related to learning process, he cultural aspect influences into child's reading habits; all these aspects haven't been adequately stimulated, which has caused a lack of interest in reading, the present investigation had as objective, to improve the quality of reading through visual didactic strategies to strengthen the reading comprehension skills of the students from Seventh "C" evening section, in the Educational Unit "Mario Cobo Barona" from Ambato in the school year 2022-2023. It addresses various bibliographic sources with a focus on specialist authors. The methodological framework follows a qualitative model, as data collection techniques, it uses observation with an observation guide for students and interviews for teachers. These tools allow to obtain data that is analyzed and the results show among other aspects that children have problems such as mistakes commonly related to spelling in circumstances such as omissions, substitutions that manifest themselves in reading and writing; and regarding errors such as: irregular strokes, dysgraphia, it indicates the absence of previous skills, known them as visual perception skills, which include visual discrimination activities for their fixation and support, which affects fluency and comprehension in reading